Committee on the Status of Minority Groups in the Economics Profession: Report of Committee Activities for the 2011 Calendar Year - Mora, Marie T (American Economic Review, 2012)
Committee on the Status of Minority Groups in the Economics Profession: Report of Committee Activities for the 2011 Calendar Year by Marie T. Mora. Published in volume 102, issue 3, pages 705-09 of American Economic Review, May 2012